Determination of Foreign Direct Investment in Indonesia Development: Case Study Indonesia and Malaysia - Rahmadila, Ervina; Trirejeki, Halim; Muhdir, Ibnu (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
Foreign Direct Investment (FDI) is one of the global economic systems. FDI is able to encourage the economic development of a country quickly, but there are problems that must be faced and of course become a challenge for the host countries, namely the presence of investors is strongly influenced by the internal conditions of a country, such as economic stability, state politics, law enforcement and others. This research investigates the relationship and significance of macroeconomic variables to FDI in two countries namely Indonesia and Malaysia in the period 1989 to 2018.The method of analysis used Pooled Least Square (PLS). GDP variables have a positive but insignificant effect on the FDI levels in Indonesia and Malaysia. The test results on exports also showed the same thing that export variables give test results positive and insignificant influence on FDI variables.